2012
DOI: 10.1242/dev.080275
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine and Fgf signalling act as opposing guidance cues in formation of the lateral line primordium

Abstract: SUMMARYThe directional migration of many cell populations occurs as a coherent group. An amenable model is provided by the posterior lateral line in zebrafish, which is formed by a cohesive primordium that migrates from head to tail and deposits future neuromasts at intervals. We found that prior to the onset of migration, the compact state of the primordium is not fully established, as isolated cells with lateral line identity are present caudal to the main primordium. These isolated cells are retained in pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…This study clearly demonstrates that epibranchial placodal cells migrate (Lassiter et al, 2009) (Breau et al, 2012). Anterior to the left.…”
Section: Cellular Interactions and Molecular Cues Interaction Betweensupporting
confidence: 53%
See 4 more Smart Citations
“…This study clearly demonstrates that epibranchial placodal cells migrate (Lassiter et al, 2009) (Breau et al, 2012). Anterior to the left.…”
Section: Cellular Interactions and Molecular Cues Interaction Betweensupporting
confidence: 53%
“…We further showed that this retention is mediated by Fgf chemotactic ligands secreted by the primordium (Fig. 4) (Breau et al, 2012). This mechanism facilitates the coalescence of the placode into a compact group of migrating cells.…”
Section: Fgf Signallingmentioning
confidence: 59%
See 3 more Smart Citations